2020
DOI: 10.1016/s1473-3099(20)30244-9
|View full text |Cite
|
Sign up to set email alerts
|

The many estimates of the COVID-19 case fatality rate

Abstract: WHO. Report of the WHO-China Joint Mission on Coronavirus Disease 2019 (COVID-19). Feb 16-24, 2020. https://www.who.int/ publications-detail/report-of-the-who-chinajoint-mission-on-coronavirus-disease-2019-(covid-19) (accessed March 22, 2020).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
453
1
29

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(497 citation statements)
references
References 6 publications
14
453
1
29
Order By: Relevance
“…However, the expression of AT 2 receptor is low in healthy adults. [45] As such, Ang II's effects in adults are modulated and balanced indirectly by angiotensin II converting enzyme (ACE2), which converts Ang II into lung-protective Angiotensin-(1-7) (Ang- [1][2][3][4][5][6][7]), similar to effects seen from AT 2 receptor stimulation. [41,46] Conceptually grouping pathways into an Ang II/AT 1 receptor and its opposing pathway ACE2/Ang-(1-7) helps with understanding the countering forces and the sequelae when an imbalance occurs.…”
Section: Angiotensin II / At 1 Receptor Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expression of AT 2 receptor is low in healthy adults. [45] As such, Ang II's effects in adults are modulated and balanced indirectly by angiotensin II converting enzyme (ACE2), which converts Ang II into lung-protective Angiotensin-(1-7) (Ang- [1][2][3][4][5][6][7]), similar to effects seen from AT 2 receptor stimulation. [41,46] Conceptually grouping pathways into an Ang II/AT 1 receptor and its opposing pathway ACE2/Ang-(1-7) helps with understanding the countering forces and the sequelae when an imbalance occurs.…”
Section: Angiotensin II / At 1 Receptor Relationshipmentioning
confidence: 99%
“…[1][2][3] (At time of article submission). While early estimates vary and true values remain uncertain, mortality is estimated between 0.4 to 3.4% [4,5] with initial morbidity and mortality disproportionally affecting older patients. [6] Infectivity (R 0 ) is estimated at 2.24 to 3.58.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality estimates are influenced by the transmissibility rate (basic reproduction number), availability of diagnostic tools, notification policies, asymptomatic presentations of the disease, resources for disease prevention and control and treatment facilities. Even with more than 1,359,398 people infected as of April 7, 2020 [4], variability in the mortality rate fits the pattern of emerging infectious diseases [38]. Furthermore, the reported cases do not consider asymptomatic cases, mild cases where individuals have not sought medical treatment, and the fact that many countries have limited access to diagnostic tests or have implemented testing policies only very recently [39].…”
Section: Discussionmentioning
confidence: 99%
“…patient from day 5 recovered or dead on day 19 and so on. Case fatality rate (F) values of COVID-19 is differed in different studies (29)(30)(31), however to avoid the regional confinement, here in this study WHO reported COVID-19 case fatality rate (F) 3.4% (3) was used. This pointed that the death from the cases day 0 is 0.034 (1×3.4%) on day 14, as opposed to be recovered 0.966 people.…”
Section: Adjust the Values Of Different Parameters From Epidemiologicmentioning
confidence: 99%